Fenofibrate protects endothelial cells against the harmful effects of TNF-alpha - Westcott, Corli; Genis, Amanda; Mthethwa, Mashudu; Graham, Roxanne; van Vuuren, Derick; Huisamen, Barbara; Strijdom, Hans (SA Heart Journal, 2017)
Introduction: Fenofibrate exerts pleiotropic effects on endothelial cells (ECs) by, amongst others, increasing nitric oxide (NO) production. We aimed to investigate fenofi brate’s putative beneficial actions in healthy or TNF-alpha-induced dysfunctional ECs. Methods: Fenofi brate-induced pro-vasodilatory responses were assessed in aortic rings (50 - 125μM; 30min) with and without L-NMMA (100μM). Rat cardiac microvascular ECs were treated with fenofibrate (30 and 50μM; 1h). In the pre-treatment experiments, fenofibrate (50μM) was administered one hour before TNFalpha treatment (20ng/ml; 24h). NO-production (DAF-2/DA or Griess assay), mitochondrial ROS-production (MitoSox™), cell viability (propidium iodide staining), and changes in the expression/phosphorylation of critical endothelial proteins were measured by Western blotting. Results: Fenofibrate increased NO-production ˜2-fold in healthy ECs (p<0.05 vs. vehicle). A ˜23% pro-vasodilatory response was induced in aortic rings, which was reversed by L-NMMA (p<0.05 vs. fenofibrate). Fenofibrate pretreatment ameliorated TNF-alpha-induced endothelial dysfunction by reversing the loss of NO, improving oxidative stress, restoring cell viability and preventing caspase-3 activation. Protective effects were underpinned by ˜47% and ˜49% up-regulation of activated eNOS and AMP-kinase, respectively (p<0.05 vs. TNFalpha). Conclusions: Fenofibrate protects TNF-alpha-induced dysfunctional ECs via up-regulated eNOS-NO, reduced oxidative stress and improved cell viability. These novel findings warrant further investigations to explore the potential use of fenofibrate as an anti-endothelial dysfunction therapeutic agent.